Improving Students’ Listening Comprehension on English Proficiency Test Through Podcast - Septika Ariyanti; Defy Gustianing (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
English Proficiency Test is a test that must be taken by students as one of the graduation requirements. With the low scores in the Listening Comprehension section, efforts are needed to improve students' listening skills in taking the English Proficiency Test. The purpose of this study is to improve students' listening skills through podcasts, so that they can help students get optimal scores. The method applied in this study is by conducting classroom action research which is one of the problem-solving strategies that utilizes real actions and the process of developing abilities in detecting and solving problems. The results of this study indicate that there is. The increase in the average score from 56.67 in Cycle I to 63.125 in Cycle II shows that the learning process implemented using podcast media has provided quite significant results in improving students' listening skills.